Modes of cell death induced by tetrahydroisoquinoline-based analogs in MDA-MB-231 breast and A549 lung cancer cell lines - Nel M; Joubert AM; Dohle W; Potter BVL; Theron AE (Dove Medical Press, 2018)
Marcel Nel,1 Anna M Joubert,1 Wolfgang Dohle,2 Barry VL Potter,2 Anne E Theron1 1Department of Physiology, Faculty of Health Sciences, University of Pretoria, Pretoria, South Africa; 2Medicinal Chemistry & Drug Discovery, Department of Pharmacology, University of Oxford, Oxford, UK Background: A and B rings of the steroidal microtubule disruptor, 2-methoxyestradiol, and its analogs can be mimicked with a tetrahydroisoquinoline (THIQ) core. THIQs are cytotoxic agents with potential anticancer activities. The aim of this in vitro study was to investigate the modes of cell death induced by four nonsteroidal THIQ-based analogs, such as STX 2895, STX 3329, STX 3451 and STX 3450, on MDA-MB-231 metastatic breast and A549 epithelial lung carcinoma cells.Materials and methods: Cytotoxicity studies determined the half-maximal growth inhibitory concentration of the analogs to be at nanomolar concentrations without the induction of necrosis. Light and fluorescent microscopy determined that compounds caused microtubule depolymerization and displayed morphological hallmarks of apoptosis.Results: Flow cytometric analyses confirmed apoptosis induction as well as an increased G2/M phase on cell cycle analysis. Furthermore, intrinsic pathway signaling was implicated due to increased cytochrome c release and a decrease in mitochondrial transmembrane potential. Potential involvement of autophagy was observed due to increased acidic vacuole formation and increased aggresome activation factor.Conclusion: Thus, it can be concluded that these four THIQ-based analogs exert anti-proliferative and antimitotic effects, induce apoptosis and involve autophagic processes. Further investigation into the efficacy of these potential anticancer drugs will be conducted in vitro and in vivo. Keywords: cancer, apoptosis, autophagy, antimitotic, nonsteroidal